2021
DOI: 10.3390/su132313211
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients and Energy Digestibility of Microalgal Biomass for Fish Feed Applications

Abstract: Aquafeed accounts for at least 75–90% of aquaculture’s operating costs. Traditional aquafeed ingredients such as fishmeal, fish oil, and soybean meal are unsustainable; further, their increasing cost necessities developing alternative feed ingredients. Microalgae-based aquafeed is not only environmentally friendly, but it can also be cost-effective with proper optimization. In addition, the nutrition profile of microalgae is similar to that of many fishes. The digestibility of a feed is one of the most importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 105 publications
0
18
0
Order By: Relevance
“…Protein digestibility of microalgae varies from 50% to 94% in different fish species. Protein digestibility of rainbow trout, Nile tilapia, European seabass, and African catfish has been reported to exceed 80% [ 110 ]. In African catfish and Nile tilapia, bead milling improved N. gaditana protein digestibility by 16 and 17 %, respectively [ 86 ].…”
Section: Microalgae As Fish Mealmentioning
confidence: 99%
See 3 more Smart Citations
“…Protein digestibility of microalgae varies from 50% to 94% in different fish species. Protein digestibility of rainbow trout, Nile tilapia, European seabass, and African catfish has been reported to exceed 80% [ 110 ]. In African catfish and Nile tilapia, bead milling improved N. gaditana protein digestibility by 16 and 17 %, respectively [ 86 ].…”
Section: Microalgae As Fish Mealmentioning
confidence: 99%
“…exhibited significantly lower mino acid digestibility than juvenile European seabass. Pretreatment would break down larger proteins into peptides and individual amino acids, which increases amino acid digestibility [ 110 ].…”
Section: Microalgae As Fish Mealmentioning
confidence: 99%
See 2 more Smart Citations
“…The whole biomass of microalgae or their specific metabolites could be used as aqua and animal feed [115]. Recently, it has been reported that microalgal nutritional compounds are ideal for the diet of cattle, chicken, goats, and pigs for the improvement in meat grade with higher PUFAs, especially EPA and DHA, and amino acids [116].…”
Section: Marine Microalgae As Feed For Aquatic and Terrestrial Animalsmentioning
confidence: 99%